Bangladesh : Selected Issues. (IMF Staff Country Reports; Country Report ;, 1999)
This Selected Issues paper analyzes the reforms in the energy sector in Bangladesh. It assesses the fiscal position of Bangladesh and examines its fiscal sustainability using a simple measure based on the debt dynamics. It concludes that although Bangladesh has so far maintained its sustainability mainly owing to the large portion of foreign financing with highly concessional interest rates, the potential fiscal burdens related to the structural problems in the banking sector and state-owned enterprises might threaten sustainability.